An ergonomic design process for a US transit bus operator workstation. (4th August 2014) - You, H.; Bucciaglia, J.; Lowe, B.; Gilmore, B.J.; Freivalds, A.
A bus operator workstation design neglecting ergonomic features can cause undesirable effects, such as overall discomfort and increased injuries. This paper presents a systematic design process for an ergonomic workstation. In the design process, the design scope is clarified by utilising the selection of an appropriate datum point and design criteria, the definition of standard bus driving postures, and the construction of hierarchies of the design and anthropometric variables. The relational attributes between the design and anthropometric variables are evaluated by a relationship analysis, and then utilised for the formulation of functional design relationships in conjunction with the geometrical configuration. These functional design relationships effectively present the interdependency of the workstation elements and enhance the flexibility of the acquired design knowledge. The design guidelines are recommended based on the functional design relationships and compared to results of other similar studies. Finally, the design guidelines are verified by a laboratory–based mockup which is evaluated by 103 jurors.